Legal Politics in the Perspective of the Constitutional Court's Decision on Presidential and Vice Presidential Candidates - Milenia Ramadhani (PT FORMOSA CENDEKIA GLOBAL, 2024)
The Constitutional Court Decision Number 90/PUU-XXI/2023 regarding the age requirements for presidential and vice presidential candidates is an important event in the context of political law in Indonesia. This event gave rise to various legal and political responses and consequences in this country. The article aims to explain the journey and dynamics of the Constitutional Court's decision along with the legal consequences and political impacts that result. The research method is normative juridical research and literature study. Data collection was carried out through library research and study of relevant legal sources. Data were analyzed qualitatively based on relevant legal and library sources. The research results show that the legal and political dynamics that occur in relation to the Constitutional Court's decision regarding the age requirements for presidential and vice presidential candidates are part of a close legal and political relationship. The legal consequence that occurs is that everyone must implement the decision because the Constitutional Court's decision is final and binding and the technical regulations need to be prepared. The resulting political impact was a significant change in the political map. Key words: Constitutional Court, Political law, Presidential election.